HUBUNGAN DUKUNGAN KELUARGA TERHADAP KUNJUNGAN KE POSYANDU PADA LANSIA DI WILAYAH KERJA PUSKESMAS BATANGTORU - Siregar, Hotma Royani; Sinambela, Desi Astuti; Siagian, Rizki Fadilla (Jurnal Kesehatan Ilmiah Aufa Royhan, 2016)
The elderly population (aged) at this time is increasing, therefore the government hasformulated a variety of health care policy for the elderly is intended to improve the healthand quality of life of the elderly to reach old age happily and efficiently in family andcommunity life in accordance with its existence, The purpose of this study to analyze therelationship of Family Support Visiting health center for Elderly. The study design useddescriptive correlation. There was 36 samples in based on criteria. The samplingtechnique used purposive sampling. This study was conducted in April-May 2016. Datawere collected using a questionnaire. Analysis of data using alternative test KolmogorovSmirnov. The results of this study indicate that there is a relationship of family SupportVisiting health center for Elderly. The majority of family support that supports the elderlyliveliness to posyandu namely (55.55%). The Relationships of Family Support Visitinghealth center for Elderly analyzed the results of a significant level of 0.002 (p <0.05). Theresults of this study can be used to observe The Relationships of Family Support Visitinghealth center for Elderly.